Ousted Egyptian President Morsi in United States Media: A framing analysis of "The Washington Post” and "The New York Times" - Halawa, Salma Hisham (AUC Knowledge Fountain, 2013)
This study investigates the portrayal of the former Egyptian President, Mohamed Morsi, in the leading American press during six critical events that took place throughout his first six months of presidency. The study reviews coverage of Mr. Morsi’s presidency in two premier daily U.S. newspapers, The New York Times and The Washington Post. Employing quantitative content analysis with framing theory as a framework, the study aims to determine how the two newspapers portrayed Mr. Morsi and to identify the employed frames and/or stereotypical words and phrases that were used to represent him. In addition, the study aims to explore U.S. foreign policy toward Egypt as characterized by the press. The study identifies six critical events that took place during Mr. Morsi’s first six months in office as elements of discussion: Mr. Morsi’s inauguration as Egypt’s new president; Mr. Morsi’s dismissal of top military leaders; Mr. Morsi’s visit to Iran for the Non-Aligned Summit Movement; Mr. Morsi’s role in brokering the Hamas-Israel ceasefire; Mr. Morsi’s release of a constitutional declaration granting himself broader powers; and the unrest in Egypt over the constitution. The total sample generated 110 news articles. The results show that, over the course of the six events, the U.S. media portrayed Mr. Morsi as a moderate Islamist leader of a significantly new era in Egyptian politics. Sometimes, the publications severely criticized Mr. Morsi’s decisions; yet, the media did not frame him as anti-American or a U.S. enemy. Additionally, it is obvious through the coverage that U.S. relations with Egypt depended purely on strategic cooperation, and not on establishing a political system that would achieve basic practices of democracy and respect for human rights.